Prevalence and Virulence Factors of Vaginal Candidiasis Among Females Collected in Tertiary Care Hospital, Khyber Pakhtunkhwa - Sadir Zaman, Naila Khan, Nazish Babar, Aroosa Zaman, Muhammad Nughman, Ayesha Gul (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The genus Candida includes about 200 different species, but only a few species are human opportunistic pathogens. Candida albicans is a commensal and opportunistic pathogenic agent that causes infection in immune compromised individuals. This work was conducted to study the detection of virulence factors of Candida spp. in clinical female samples from tertiary care hospitals of Kohat. Methods: This cross-sectional study was conducted during April to July 2017. Patients data and samples were collected from Liaqat Memorial Hospital (LMH), Fauji Foundation Hospital, and Family Health Hospital, Kohat. Morphological identification was done by using different media i.e SDA and PDA. Further identification was done through gram staining and germ tube method. Results: A total of one hundred and sixty (n=160) clinical samples were collected from outdoor patients, in which only 50 were Candida positive. Among all the 50 isolates of 13(26%) Candida spp. were germ tube positive. Further identification were done through Chrome Agar in which 17(34%) isolates were C. albicans, followed by 19(38%) were C. tropicalis, and 4(8%) isolates were C. glabrata. Detection of virulence factors is done by different methods in which 30(60%) isolates showed phospholipase activity in which 12(24%) of Candida spp. were large positive. In haemolytic activity showed 28(56%) strong haemolytic activity, 5(10%) were weak positive. Candida positive patients high 36 (72%) in 21 to 40 years. Conclusion: In the present study, the results concluded that patient infected with Candida are highly virulent as about more than 60% of Phospholipase, Biofilm and Haemolytic positive. Candida species have high prevalence rate among 21 t0 40 years from the rest of very late and early age. Finding novel antibacterial chemicals is highly advised in view of the study’s findings. Additionally, it is crucial to assess the candida resistant patterns at the genomic and proteomic levels in order to identify the genes causing the patterns of antibiotic resistance. Keyword: Candida, Virulence Factors, Germ Tube, Chrome Agaropportunistic pathogens, Haemolytic positive, Gram staining, Germ tube method.